2017
DOI: 10.1515/amm-2017-0356
|View full text |Cite
|
Sign up to set email alerts
|

Composite Coatings of Chromium and Nanodiamond Particles on Steel

Abstract: Chrome plating is used to improve the properties of metal surfaces like hardness, corrosion resistance and wear resistance in machine building. To further improve these properties, an electrodeposited chromium coating on steel, modified with nanodiamond particles is proposed. The nanodiamond particles (average size 4 nm measured by TEM) are produced by detonation synthesis (NDDS). The composite coating (Cr+NDDS) has an increased thickness, about two times greater microhardness and finer microstructure compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The electrochemical chromium coatings, modified with diamond nanoparticles, deposited on wrought steel, sintered steel and other metals and alloys increase several times their hardness, wear and corrosion resistance in comparison to the monochromium coatings. Our studies unambiguously showed the influence of the diamond nanoparticles in improvement of the chemical and mechanical properties of the composite Cr + ND coatings [1][2][3]. The role of the diamond nanoparticles in the built-up of the coatings and their presence in the layer are controversial.…”
Section: Introductionmentioning
confidence: 68%
“…The electrochemical chromium coatings, modified with diamond nanoparticles, deposited on wrought steel, sintered steel and other metals and alloys increase several times their hardness, wear and corrosion resistance in comparison to the monochromium coatings. Our studies unambiguously showed the influence of the diamond nanoparticles in improvement of the chemical and mechanical properties of the composite Cr + ND coatings [1][2][3]. The role of the diamond nanoparticles in the built-up of the coatings and their presence in the layer are controversial.…”
Section: Introductionmentioning
confidence: 68%
“…New chemical treatment in acid -alkaline solution was applied on the surface of the samples 7* and 8* in order to improve the de-oxidation process. Our previous research [4] shows that the presence of diamond nanoparticles (NDDS) in the electrolyte increase the metal deposition. Samples 8 and 8* were prepared from electrolyte containing 10 g/l NDDS.…”
Section: Fig 1 Rectangular and Cylindrical Samples Uncoated And Coate...mentioning
confidence: 99%
“…The use of electroplated silver on electronic components is well established and continues to expand into new applications such as on waveguides for cellular telecommunications systems [3]. Depending on the application the thickness of the layer may vary from 2 to 24 µm [4]. Also a technology of depositing silver on aluminum using cyanide baths is proposed [5].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many efforts have been done to increase corrosion resistance and stability of steel materials [3,4]. There are different corrosion protection methods including cathodic/anodic protection, coatings, inhibitors and proper design [5][6][7][8]. Surface treatment is a generic way to protect metals from corrosion, which includes physical vapor deposition, chemical conversion coating, electroless and electroplating and so on [9,10].…”
Section: Introductionmentioning
confidence: 99%